Comportamento de híbridos de milho adubados com nitrogênio e inoculados com diazotróficos associativos - Morais, Gildean Portela (2014)
The development of new technologies that seek to reduce the use of fertilizers, especially nitrogen, is essential for the sustainability of the production system in maize (Zea mays L.). The use of microorganisms in agriculture is a widely researched alternative, seeking a reduction in the use of nitrogen fertilizers with consequent reduction in environmental degradation. This study aimed at proving the hypothesis of the effect of inoculation with endophytic diazotrophic bacteria on growth and nutrient content in two maize hybrids subjected to four levels of nitrogen fertilization and on the soil microbial activity. The experiment was conducted in a greenhouse for a period of 90 days. The experimental design was randomized blocks, evaluating two maize hybrids (AG 1051 and BM 3061), the treatments were arranged in a 4 x 2 factorial design, with four replicates, inoculated and not inoculated with the commercial product based on Azospirillum brasilense and subjected to four different doses of nitrogen (0, 0.5, 1.0 and 1.5 g pot-1). In this trial, there was a significant interaction between inoculation factors and nitrogen doses root nitrogen accumulation and shoot phosphorus accumulation of the hybrid AG 1051. Regarding the BM 3061 hybrid, it showed a significant interaction on the shoot potassium accumulation. In the assessment, there have been isolated factors of inoculation and nitrogen doses for root dry mass, the accumulation of nitrogen and potassium of shoots for AG 1051. For BM 3061 hybrid, there were significant effects of phosphorus content of shoots and root potassium. The isolated factor of inoculation with Azospirillum brasilense showed significant effect only on the basal soil respiration under the influence of the hybrid BM 3061. Data on height, stem diameter, leaf area, chlorophyll content, dry mass of leaves, stems and roots of maize plants grown under greenhouse conditions showed significant effects attributed solely to the addition of nitrogen fertilizer, regardless of inoculation with Azospirillum brasilense. It was concluded that inoculation with Azospirillum brasilense in this study contributed little to the parameters evaluated, the maize hybrid AG 1051 was more sensitive to the inoculation with BM 3061, and that the maize hybrids are sensitive to the variation of the nitrogen content applied to the soil.